Association of nuclear factor-kappa B1 (NF-kB1) Ins/Del gene polymorphism with Hepatitis C virus outcomes - Shaimaa Rahem Al-Salihy; Refif Sabeeh Al-Shawk; Safaa Abdul-Karim Al-Waysi; Maarib Nazih Rasheed (Journal of the Pakistan Medical Association, 2024)
Objective: To explore the association of nuclear factor-kappa B1 polymorphism in the promotor area of the gene with hepatitis C virus infection outcomes. Method: The case-control study was conducted at the Hepatology and Gastroenterology Teaching Hospital, Baghdad, Iraq, from Dec 1, 2020, to Aug 30, 2021, and comprised individuals ages 20-68 years. Group 1 had patients with persistent hepatitis C virus infection, group 2 had subjects with spontaneous hepatitis C virus clearance, group 3 had subjects treated with direct-acting antiviral drugs, and group 4 had healthy controls. Venous blood was collected for polymorphism genetic analysis of nuclear factor-kappa B1 insertion/deletion ATTG (Adenine-Thymine- Thymine-Guanine) at rs28362491 using a high-resolution melting technique. Data was analysed using SPSS 27. Results: Of the 88 subjects, there were 22(25%) in each of the 4 groups. Overall, there were 55(62.5%) females and 33(37.5%) males, and 40(45.45%) were aged 20-39 years while 48(54.54%) were aged 40-68 years (p>0.05). The Ins allele of rs28362491 was significantly more frequent in the patients than in controls (p=0.0053). The carriage of rs28362491 insertion/insertion and insertion/deletion genotypes, compared to wild-type homozygous deletion/deletion, had a significantly higher risk of developing hepatitis C virus infection (p=0.0013). No association was found between rs28362491 and spontaneous hepatitis C virus clearance (p>0.05). Conclusion: The insertion allele of rs28362491 was found to be associated with increased susceptibility to developing hepatitis C virus infection. Key Words: Antiviral, Gastroenterology, Hepaciviral, Thymine, Alleles, Homozygote, Hepatitis C, Chronic, Adenine, Guanine.